Comparison of split double and triple twists in pair figure skating - King, D. L.; Smith, S. L.; Brown, M. R.; McCrory, J. L.; Munkasy, B. A.; Scheirman, C. I. (Sports Biomechanics, 2008)
In this study, we compared the kinematic variables of the split triple twist with those of the split double twist to help coaches and scientists understand these landmark pair skating skills. High-speed video was taken during the pair short and free programmes at the 2002 Salt Lake City Winter Olympics and the 2003 International Skating Union Grand Prix Finals. Three-dimensional analyses of 14 split double twists and 15 split triple twists from eleven pairs were completed. In spite of considerable variability in the performance variables among the pairs, the main difference between the split double twists and split triple twists was an increase in rotational rate. While eight of the eleven pairs relied primarily on an increased rotational rate to complete the split triple twist, three pairs employed a combined strategy of increased rotational rate and increased flight time due predominantly to delayed or lower catches. These results were similar to observations of jumps in singles skating for which the extra rotation is typically due to an increase in rotational velocity; increases in flight time come primarily from delayed landings as opposed to additional height during flight. Combining an increase in flight time and rotational rate may be a good strategy for completing the split triple twist in pair skating.